(3eQGLYI GdMSGHGJ Hjf GdfXQjI h GdJWHjb (B/s - (3LQHhY, jhSa eMehOs ((3YeGf(B: s (3OGQ GdhQGb ddfTQ h GdJhRjY(B, s, 2007)
(3jJfGhd gPG GdcJGH GdeONd aj JObjb GdMSGHGJ (B- (3GfhGY eQGLYI GdMSGHGJ (B- (3JUMjM GdGNWGA (B- (3GdeYGjjQ GdegfjI deQLYI GdMSGHGJ (B- (3bhGYO GdSdhc Gdegfj (B- (3eSDhdjGJ hMbhb eQGLY GdMSGHGJ (B- (3GdGJLGgGJ GdMOjKI aj eQGLYI GdMSGHGJ (B- (3eQGLYI GdYedjGJ GdJLGQjI (B- (3eQGLYI GdYedjGJ GdUfGYjIs
(3HjHdjhZQGajG U(B.713s
Keywords: (3GdeMGSHIs; (3GdeYGjjQ GdeQGLYIs; (3eQGLYI GdMSGHGJs